THE EVALUATION OF THE COURSE BOOKS USED IN TEACHING TURKISH AS A FOREIGN LANGUAGE IN TERMS OF WORD TEACHING METHODS - Ahmet Tayfun ÖZTÜRK; Kürşat İLGÜN (International Journal of Eurasia Social Sciences, 2024)
Abstract In teaching Turkish as a foreign language, it is aimed for learners to communicate effectively from the beginning of the teaching process. Learners can communicate with words, idioms, proverbs, and phrases that make up the vocabulary they have learned during the learning process. Learners can develop receptive and productive language skills to the extent that they increase their vocabulary. For this reason, textbooks, which are the most frequently and most used teaching materials in teaching Turkish as a foreign language, are the most important sources that guide vocabulary teaching process. In other words, textbooks are the most basic and decisive materials that decide the number of words, their suitability for the level and in which context they will be used. In this respect, the use of the right strategies, methods and techniques in the vocabulary teaching process is seen as an important factor in the realization of language development at the intended level in teaching Turkish as a foreign language. Because the right strategies, methods and techniques in teaching vocabulary directly contribute to the learner’s learning, functional use, and internalization of words. It is important for the realization of learning goals that the vocabulary teaching methods to be used in teaching Turkish as a foreign language are diverse, effective, and functional, and that the learners are suitable for their learning styles, individual differences, and language learning levels. The realization of these features in the learning process also contributes to the learner’s motivation to learn a language. The fact that the vocabulary teaching methods in the textbooks are monotonous, boring, and not suitable for the level poses a problem in reaching the objectives in vocabulary teaching. In this study, it is aimed to determine the vocabulary teaching methods applied in the A1, A2, B1, B2 and C1 level textbooks of Yedi İklim Turkish Teaching Set (YİTÖS), Istanbul Turkish Teaching Set for Foreigners (İTÖS) and Gazi University Turkish Teaching Set (GÜTÖS), which are the most widely used sources in teaching Turkish as a foreign language. Significant differences emerged in the numerical distribution of vocabulary teaching activities in the relevant textbooks, and it was determined that some methods/techniques were not used at all, while others varied proportionally according to the textbooks.